Modern challenges to Islamic law / Shaheen Sardar Ali. - Ali, Shaheen Sardar (Law in context., 2016)
The diversity of interpretation within Islamic legal traditions can be challenging for those working within this field of study. Using a distinctly contextual approach, this book addresses such challenges by combining theoretical perspectives on Islamic law with insight into how local understandings impact on the application of law in Muslim daily life. Engaging with topics as diverse as Islamic constitutionalism, Islamic finance, human rights and internet fatawa, Shaheen Sardar Ali provides an invaluable resource for scholars, students and practitioners alike by exploring exactly constitutes Islamic law in the contemporary world. Useful examples, case studies, a glossary of terms and the author's personal reflections accompany traditional academic critique, and together offer the reader a unique and discerning discussion of Islamic law in practice.